Quantitative single-molecule localization microscopy (qSMLM) of membrane proteins based on kinetic analysis of fluorophore blinking cycles - Fricke, Franziska; Beaudouin, Joël; Eils, Roland; Heilemann, Mike (Super-resolution microscopy, 2017)
Photoswitchable or photoactivatable fluorophores are the key in single-molecule localization microscopy. Next to providing fluorescence images with subdiffraction spatial resolution, additional information is available from observing single fluorophores over time. This includes the characteristic photophysical phenomenon of “blinking” that is exhibited by single fluorescent proteins or fluorophores and follows well-defined kinetic laws. Analyzing the kinetics of “blinking” allows determining the number of fluorophores in a multi-molecular complex. As such, quantitative information at the molecular level can be extracted, representing a tremendously useful extension of single-molecule super-resolution microscopy. This concept is in particular useful to study homo- and heterooligomeric signaling protein complexes in the plasma membrane of an intact cell with molecular resolution. Here, we provide an experimental framework for deciphering the stoichiometry of membrane proteins on the basis of SMLM and photoswitching statistics.